Geography and Development. - Venables, A; Shalizi, Z; Henderson, J (World Bank, 2000)
September 2000 Why are spatial differences in land rents and wages not bid away by firms and individuals in search of low-cost or high-income locations? Why does economic activity cluster in centers of activity? And what are the consequences of remoteness from existing centers? The most striking fact about the economic geography of the world is the uneven spatial distribution of economic activity, including the coexistence of economic development and underdevelopment. High-income regions are almost entirely concentrated in a few temperate zones, half of the world's GDP is produced by 15 percent of the world's population, and 54 percent of the world's GDP is produced by countries occupying just 10 percent of the world's land area. The poorest half of the world's population produces only 14 percent of the world's GDP, and 17 of the poorest 20 nations are in tropical Africa. The unevenness is also manifest within countries and within metropolitan concentrations of activity. Why are these spatial differences in land rents and wages not bid away by firms and individuals in search of low-cost or high-income locations? Why does economic activity cluster in centers of activity? And what are the consequences of remoteness from existing centers? Henderson, Shalizi, and Venables argue that understanding these issues is central for understanding many aspects of economic development and underdevelopment at the international, national, and subcontinental levels. They review the theoretical and empirical work that illuminates how the spatial relationship between economic units changes and conclude that geography matters for development, but that economic growth is not governed by a geographic determinism. New economic centers can develop, and the costs of remoteness can be reduced. Many explicit policy instruments have been used to influence location decisions. But none has been systematically successful, and many have been very costly-in part because they were based on inappropriate expectations. Moreover, many ostensibly nonspatial policies that benefit specific sectors and households have spatial consequences since the targeted sectors and households are not distributed uniformly across space. These nonspatial policies can sometimes dominate explicitly spatial policies. Further work is needed to better understand these dynamics in developing countries. This paper-a product of Infrastructure and Environment, Development Research Group-is part of a larger effort in the group to analyze the role of economic geography and urbanization in the development process. Zmarak Shalizi may be contacted at zshalizi@worldbank.org.